(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Our educational system has advanced to the level of public policy in our country, ensuring that our children acquire modern knowledge and professions in conditions that meet world standards, ensuring the maturation of physically and spiritually mature people, realization of their abilities and talents, intellectual potential, perfection of loyalty and dedication to the country. The public education system has also seen good developments in the recent five years as a consequence of numerous innovations and reforms. The reforms and innovations in higher education are discussed and studied in this article.